Evaluation of antinociceptive and antipyretic effect of Pupalia lappacea Juss (International Current Pharmaceutical Journal, 2013)
Pupalia lappacea Juss (Family: Amaranthaceae) is claimed to be useful in treatment of bone fracture, wounds, boils, cough, toothache, fever and malaria. The study was aimed to evaluate the 80% aqueous ethanolic extract of aerial parts of P. lappacea for antinociceptive and antipyretic activities to verify the traditional claim. The extract was orally administered at doses of 200, 400 and 600 mg/kg. The extract has significantly (P